Cross-border banking: Challenges for deposit insurance and financial stability in the European Union - Robert A. Eisenbeis; George G. Kaufman (Federal Reserve Bank of Atlanta, 2007)
This paper examines the implications that alternative regulatory structures may have for resolving failed banking institutions. We place our emphasis on the European Union (EU), which is both economically and financially large and has several features relating to cross-border banking in the form of direct investment that may heighten the problems we consider. We propose four principles to ensure the efficient resolution of bank failures, should they occur, with minimum, if any, credit and liquidity losses. These principles include prompt legal closure of institutions before they become economically insolvent, prompt identification of claims and assignment of losses, prompt reopening of failed institutions, and prompt recapitalizing and reprivatization of failed institutions. Finally, we propose a mechanism to put such a scheme into place quickly in the case where a cross-border banking organization seeks to take advantage of the liberal cross-border branching provisions in the single banking license available to banks in the EU. In return for the privilege of such a license, the bank agrees to be subject to a legal closure rule as a positive capital ratio established by the EU or the home country.
Keywords: G28; G33; G38; D74; D83; G21; 330; cross-border banking; financial crises; bank regulatory structure; branching; banking subsidiaries; supervision and regulation